THE EFFECT OF SOCIAL MEDIA MARKETING ON GAMIFICATION AND WILLINGNESS TO PAY A PREMIUM A GENERATIONAL DIFFERENCES - Tri Tata Wilia; Pristiyanilicia Putri; Arika Juwita Z; Weri Sirait; Havid Syafwan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study investigates the influence of social media marketing on gamification and the willingness to pay premiums, specifically within the context of "Ojol the Game Premium." The research aims to explore how social media marketing strategies affect user engagement and the factors that drive users to pay for premium features. A quantitative approach was employed, utilizing partial least squares structural equation modelling (PLS-SEM) 4.0 to analyze the data collected from a targeted sample of users. The findings indicate that effective social media marketing significantly enhances user participation through gamification, which in turn increases the willingness to pay premiums. This study also sheds light on the essential role of targeted marketing efforts in influencing user behavior. The implications of this study are valuable for researchers and practitioners in understanding the dynamics of social media marketing, gamification, and premium pricing strategies. Future research could expand the scope by considering other variables or broader populations. Keywords: Social Media Marketing; Gamification; Premium Pricing; Generation Z and Y; Online Games.   Abstrak: Studi ini menyelidiki pengaruh pemasaran media sosial terhadap gamifikasi dan kesediaan membayar fitur premium, khususnya dalam konteks "Ojol the Game Premium". Penelitian ini bertujuan untuk mengeksplorasi bagaimana strategi pemasaran media sosial mempengaruhi keterlibatan pengguna dan faktor-faktor yang mendorong pengguna untuk membayar fitur premium. Pendekatan kuantitatif digunakan, dengan memanfaatkan pemodelan persamaan kuadrat terkecil parsial (PLS-SEM) 4.0 untuk menganalisis data yang dikumpulkan dari sampel pengguna yang ditargetkan. Temuan menunjukkan bahwa pemasaran media sosial yang efektif secara signifikan meningkatkan partisipasi pengguna melalui gamifikasi, yang pada pasangannya meningkatkan kesediaan membayar fitur premium. Studi ini juga menjelaskan peran penting upaya pemasaran yang diharapkan dalam mempengaruhi perilaku pengguna. Implikasi dari studi ini berharga bagi peneliti dan praktisi dalam memahami dinamika pemasaran media sosial, gamifikasi, dan strategi penetapan harga premium. Penelitian selanjutnya dapat memperluas cakupannya dengan mempertimbangkan variabel lain atau populasi yang lebih luas. Kata kunci: Pemasaran Media Sosial; Gamifikasi; Penetapan Harga Premium; Generasi Z dan Y; Permainan Online.